Associations between asthma trigger reports, mental health conditions, and asthma morbidity among world trade center rescue and recovery workers. (3rd August 2019) - Morales-Raveendran, E.; Goodman, E.; West, E.; Cone, J.E.; Katz, C.; Weiss, J.; Feldman, J.M.; Harrison, D.; Markowitz, S.; Federman, Alex; Wisnivesky, J.P.
Abstract: Aim : There is limited information regarding asthma triggers in World Trade Center (WTC) rescue and recovery workers (RRW) or how mental health conditions affect the perception of triggers. Methods : We included 372 WTC workers with asthma. The Asthma Trigger Inventory (ATI) assessed triggers along five domains: psychological, allergens, physical activity, infection, and pollution. We administered the Structured Clinical Interview to diagnose post-traumatic stress disorder (PTSD), major depression and panic disorder (PD). The Asthma Control Questionnaire (ACQ) and Mini Asthma Quality of Life Questionnaire (AQLQ) measured asthma control and quality of life, respectively. Linear regression models were fitted to examine the association of ATI total and subdomain scores with mental health conditions as well as the percent of ACQ and AQLQ variance explained by ATI subscales. Results : The most common triggers were air pollution (75%) and general allergens (68%). PTSD was significantly associated with psychological triggers (partial r 2 =0.05, p  < 0.01), physical activity (partial r 2 =0.03, p  < 0.01) and air pollution (partial r 2 =0.02, p  = 0.04) subscales while PD was significantly associated with air pollution (partial r 2 =0.03, p  = 0.03) and general allergens (partial r 2 =0.02, p  = 0.03). ATI subscales explained a large percentage of variance in asthma control (r 2 =0.37, p  < 0.01) and quality of life scores (r 2 =0.40, p  < 0.01). Psychological subscale scores explained the largest portion of the total variability in ACQ (partial r 2 = 0.11, p  = 0.72) and AQLQ (partial r 2 =0.14, p  = 0.64) scores. Conclusion : RRW with mental health conditions reported more asthma triggers and these triggers were associated with asthma morbidity. These data can help support interventions in RRW with asthma.